Chemoprevention of Head and Neck Cancer with Celecoxib and Erlotinib: Results of a Phase Ib and Pharmacokinetic Study - Saba, Nabil F.; Hurwitz, Selwyn J.; Kono, Scott A.; Yang, Chung S.; Zhao, Yang; Chen, Zhengjia; Sica, Gabe; Müller, Susan; Moreno-Williams, Rachel; Lewis, Melinda; Grist, William; Chen, Amy Y.; et al. (Cancer prevention research (Philadelphia, Pa.), 2014)
Epidermal growth factor receptor (EGFR) and COX-2 inhibitors synergistically inhibit head and neck squamous cell carcinoma tumorigenesis in preclinical studies. We conducted a phase I and pharmacokinetic study with the erlotinib and celecoxib combination in patients with advanced premalignant lesions. Thirty-six subjects with oral leukoplakia, mild, moderate, or severe dysplasia, or carcinoma in situ were screened for study participation; 12 consented and received therapy for a median of 5.38 months. Erlotinib was escalated following a standard 3+3 design at 50, 75, and 100 mg orally daily and celecoxib was fixed at 400 mg twice daily for 6 months. Biopsy of lesions and cytobrush of normal mucosa were performed at baseline, 3, 6, and 12 months. Erlotinib pharmacokinetics were analyzed in 10 subjects. The maximum tolerated dose of erlotinib with celecoxib 400 mg BID was 50 mg per day with skin rash being the main observed toxicity. Overall histologic response rate was 63% (complete response, 43%; partial response, 14%; stable disease, 29%; and disease progression, 14%). With median follow-up of 36 months, mean time to progression to higher-grade dysplasia or carcinoma was 25.4 months. Downregulation of EGFR and p-ERK in follow-up biopsies correlated with response to treatment. Larger average erlotinib V/F (approximately 308 L) and CL/F (8.3 L/h) compared with previous studies may be related to relatively large average bodyweights. Average erlotinib t1/2 was 25.6 hours. Encouraging responses to the celecoxib and erlotinib combination correlated with EGFR pathway inhibition. Although erlotinib-related rash was the main limitation to dose escalation, the intervention was well tolerated. Cancer Prev Res; 7(3); 283–91. ©2013 AACR.